2020
DOI: 10.1186/s12937-020-00601-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spinach-derived thylakoid supplementation in combination with calorie restriction on anthropometric parameters and metabolic profiles in obese women with polycystic ovary syndrome: a randomized, double-blind, placebo-controlled clinical trial

Abstract: Background: There is a promising outlook regarding the potential effect of spinach-derived thylakoids in the management of obesity and its associated metabolic disturbances. This research aimed to evaluate the effects of spinach-derived thylakoids supplementation combined with a calorie-restricted diet on anthropometric and metabolic profiles in obese women with the polycystic ovary syndrome (PCOS). Methods: In a 12-week double-blind placebo-controlled randomized clinical trial, 48 females with obesity and PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(82 reference statements)
1
8
0
Order By: Relevance
“… 320 CR has been found to inhibit hormone secretion in mammary glands and ovulation in females to perturb signal transduction between the pituitary gland and gonads. 321 Likewise, testosterone levels are elevated in men by CR. 322 Fasting induces profound changes in the hypothalamic-pituitary-thyroid (HPT) axis.…”
Section: Dietary Intervention In Tissue Health and Diseasementioning
confidence: 99%
“… 320 CR has been found to inhibit hormone secretion in mammary glands and ovulation in females to perturb signal transduction between the pituitary gland and gonads. 321 Likewise, testosterone levels are elevated in men by CR. 322 Fasting induces profound changes in the hypothalamic-pituitary-thyroid (HPT) axis.…”
Section: Dietary Intervention In Tissue Health and Diseasementioning
confidence: 99%
“…Recent human clinical intervention trials have assessed diverse aspects of SPI intake, including anthropometric measures, muscle fitness, metabolic profiles, arterial stiffness, and urinary biomarkers [5,[34][35][36], extending prior research on the health benefits of green leafy vegetables and the functional properties of spinach-derived phytochemicals and bioactives [37][38][39][40][41]. We reported that long-term feeding of freeze-dried SPI at 10% w/w in the diet for 26 weeks exhibited significant antitumor efficacy in the Pirc model, resulting in >60% reduced tumor multiplicity in the colon and small intestine [6].…”
Section: Discussionmentioning
confidence: 99%
“… 434 CR may also improve weight and metabolic disorders in patients with PCOS, alone or in combination with supplementation. 435 However, the exact mechanisms of these dietary interventions remain unclear and need further exploration.…”
Section: Implications Of Dietary Intervention For Other Diseasesmentioning
confidence: 99%